The Effect of Peer Assistance on Adherence to Consuming Iron Tablets and Anemia Status among Young Female Adolescents - Hasyim, Muhammad; Arief, Erdiawati; Nurbaya, Nurbaya (Poltekkes Kemenkes Palu, 2023)
Introduction: Basic Health Research stated that 76.2% of young women received iron supplements in the last 12 months, and only 2.13% of them consumed iron tablets as recommended. Anemia in adolescence causes reduced physical and mental capacity and diminished concentration in work and educational performance. Purpose: This study aimed to assess the impact of peer mentoring and its effect on tackling anemia in adolescent girls. Methods: The method used was quasy experiment and was conducted for 12 weeks from July-November 2022. The case group consisted of teenagers at SMP 1 Mamuju and the control group was at SMPN 1 Malunda 1. Results: Before the intervention, the anemia status in the case group was 19.2%, and post-intervention was 9%. The control group before intervention was 20.5%, and after intervention, it was 2.6%. There was no difference in the Hb test results for the two sample groups (p-value 0.319). After the intervention, the two sample groups had a difference in Hb changes (p-value 0.000). Conclusion: Changes in Hb before and after the intervention showed differences in the case and control groups (p-value 0.000). Peer assistance is highly recommended as one of the anemia interventions among female adolescents.